From Chaos to Clarity: A Study of Sudha Murty’s Mahashweta - C.Girija; Dr. S. Bhuvaneswari (Revista Electronica de Veterinaria, 2024)
Sudha Murty’s novel Mahashweta, addresses the challenges women face in patriarchal societies, particularly in India. The narrative explores themes of pain, marital discord, divorce, disbelief, economic independence, gender inequity, and personal empowerment. Literature has documented the silent sufferings of women throughout history. Fewer women are shown as silently accepting sufferings in unbearable situations, while others are depicted as raising their voices against injustice and facing challenges with courage. The protagonist, Anupama, suffers societal rejection and familial neglect after being identified with leukoderma. Her journey from abandonment and despair to clarity exemplifies her resilience, self-awareness, and individual strength. Through self-acceptance, education, and economic constraint, Anupama reclaims her identity and transcends societal stigma. The research paper emphasizes the importance of inner strength and independence, presenting Anupama’s transformation as a model for overcoming societal obstacles and living by personal values rather than external judgments. The novel advocates self-love, emotional well-being, and financial independence as tools for empowerment. This article reflects the broader message of valuing oneself over societal expectations and offers practical inspiration for navigating chaos in life and highlights the path to clarity through self-reliance and strength of spirit. It serves as a guide for individual’s striving to rise above societal norms and embrace a life of purpose and reliability.